PEMODELAN DAN SIMULASI REAKSI DEGRADASI PARASETAMOL DENGAN KATALIS TiO2 - I Gede Pandega Wiratama; Hendra Ronaldi; Herry Santoso (JURNAL INTEGRASI PROSES, 2017)
The objective of this experiment is to determine the model and the optimum condition of the photocatalytic degradation of paracetamol. Based on the mechanism of the process, the suggested kinetics models are pseudo homogenous model, First Unimolecular Catalytic Reaction model, and Second Unimolecular Catalytic Reaction model.The first step of this research is determining the model then estimating the parameters of the model. k and n for the pseudo homogenous model;  ksr, kads, kdes, KA, KP, KR,and KS for the First Unimolecular Catalytic Reaction and Second Unimolecular Catalytic Reaction model. The validation and simulation of the parameters are based on the results of experiments conducted in the study (Desale et al., 2013). Validation of the models are carried out under the variations of catalyst loading and pH. This research shows that Surface reaction of First Unimolecular Catalytic Reaction’s model fitted the best from the data and there is no pattern on the error. The simulation gives the optimum conditions at catalyst loading 1 g/L and pH 9. In this optimum conditions, the simulation of paracetamol degradation can reach 99.961% on the conversion.